PENINGKATAN HASIL BELAJAR IPA MENGGUNAKAN METODE INKUIRI KELAS V SEKOLAH DASAR NEGERI 03 SUTI SEMARANG - Usman, Syahril (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This study aimed to to get an idea factually on improving student learning outcomes in learning science using inquiry method in class V SD Negeri 03 Semarang Suti. The method used in this research is descriptive, form research is classroom action research, the nature of the research is a collaborative research subject is the teacher who taught in class V SDN 03 Suti Semarang, Bengkayang. Results of the study is, 1) The ability of teachers to plan learning using the inquiry method in the first cycle has an average of 2.82, the second cycle has increased an average of 3.64 and the third cycle has increased an average of 3.88. 2) The ability of teachers in implementing the learning in the first cycle with an average score of 2.68 and in cycle II increased the average score was 3.20, and the results of the third cycle has increased an average score of 3.92. 3) The results of student learning is increasing every cycle is the first cycle an average score of 57.14%, cycled II was increased an average score of 85.71% and the third cycle increase in the average score of 100% with a very good category. Â Keywords: Methods of Inquiry, Learning Outcomes, Natural Sciences